Pengaruh Pertumbuhan Ekonomi dan Pendapatan Asli Daerah Terhadap Belanja Modal pada Kota Langsa Provinsi Aceh Periode 2012-2021 - Isharyanto Isharyanto; Jadmiko Anom Husodo; Sri Wahyuni; Maria Madalina; Sunny Ummul Firdaus (Jurnal Syntax Transformation, 2022)
The Constitutional Court (MK) has read out Decision Number 91/PUU-XVIII/2020 regarding the submission of judicial review from several parties regarding Law Number 11 of 2020 concerning Job Creation (UU Cipta Kerja). The decision essentially states that the Job Creation Law is contrary to the 1945 Constitution of the Republic of Indonesia and does not have conditionally binding legal force as long as it does not mean that "no corrections have been made within 2 (two) years since the decision was pronounced." This research is a normative legal research by examining the laws and regulations and related to the social conditions that exist in society. However, the Employment Creation Law is still valid until it is established according to the grace period stipulated in the decision. If no repairs are made during the stipulated time, the Job Creation Act becomes permanently unconstitutional. Then within the time limit as determined, the legislator cannot complete the revision of the job creation law, then the job creation law is canceled and the law,